Fine-needle Aspiration Cytology to Identify a Rare Mimicker of Breast Cancer: Plasma Cell Mastitis - Ortiz-Mendoza, Carlos Manuel; Sánchez, Norma Alicia Acosta; Dircio, Arturo Catarino (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
There are rare benign diseases that can mimic malignant breast neoplasms in the clinical exam and in mammography. We evaluated the contribution of an accessible procedure to most clinicians, the fine-needle aspiration cytology, to identify a rare mimicker of malignant breast neoplasms. A type 2 diabetic 85-year-old female presented with a 6-month history of a left breast lump. The physical exam and mammography were compatible with breast cancer. Nevertheless, after fine-needle aspiration cytology, the diagnosis was plasma cell mastitis. Once this rare diagnosis was established, the tumor was extirpated, and the final histologic diagnosis corroborated chronic plasma cell mastitis. The patient's postoperative evolution was uneventful, and no other treatment was needed. Fine-needle aspiration cytology could be a valuable tool to identify rare mimickers of malignant breast neoplasms.
Keywords: cancer; breast; breast cancer; fine needle aspiration biopsy; granuloma; mammography; mastitis